Fatty Acyl Sulfonyl Fluoride as an Activity‐Based Probe for Profiling Fatty Acid‐Associated Proteins in Living Cells. (30th December 2021) - Zhang, Dong; Lu, Minghao; Chen, Chengjie; Xu, Yaxin; Peng, Tao
Abstract: Fatty acids play fundamental structural, metabolic, functional, and signaling roles in all biological systems. Altered fatty acid levels and metabolism have been associated with many pathological conditions. Chemical probes have greatly facilitated biological studies on fatty acids. Herein, we report the development and characterization of an alkynyl‐functionalized long‐chain fatty acid‐based sulfonyl fluoride probe for covalent labelling, enrichment, and identification of fatty acid‐associated proteins in living cells. Our quantitative chemical proteomics show that this sulfonyl fluoride probe targets diverse classes of fatty acid‐associated proteins including many metabolic serine hydrolases that are known to be involved in fatty acid metabolism and modification. We further validate that the probe covalently modifies the catalytically or functionally essential serine or tyrosine residues of its target proteins and enables evaluation of their inhibitors. The sulfonyl fluoride‐based chemical probe thus represents a new tool for profiling the expression and activity of fatty acid‐associated proteins in living cells. Abstract : An alkynyl‐functionalized long‐chain fatty acid‐based sulfonyl fluoride chemical probe was developed for covalent targeting, activity profiling, proteomic identification, and inhibitor evaluation of diverse classes of fatty acid‐associated proteins in living cells.